PENGARUH GAYA HIDUP TERHADAP PERILAKU MEROKOK PADA MAHASISWI SEKOLAH TINGGI ILMU EKONOMI HARAPAN (STIE-HARAPAN) MEDAN TAHUN 2012 - vidya lubis; Kintoko Rochadi; Namora Lumongga (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Health development began to face a new disease patterns, the rise in non-communicable diseases are triggered changes in people's lifestyles such as diet low in fiber and high in fat and salt and excessive sugar consumption, lack of physical activity (sports) and the prevalence of cigarette consumption continues to increase. Smoking is harmful to the health of a student, it is necessary to do research on how to Influence Lifestyle Against Smoking Behavior At School of Economics Student Expectations (STIE-Hope) Medan in 2012. Type of research is cross sectional study to investigate the effect of lifestyle on student smoking behavior. Sampling using purposive sampling criteria that students who smoked active on campus as many as 31 people. The results of this study indicate that the independent variables are the three components of lifestyle (Activities, Interests, Opinion) had a p value <0.05 so that the three independent variables had a significant influence on student smoking behavior. Of the three components of the lifestyle, the most influential variable is subjective variable with a value B of 69.610. Therefore, the Hope School of Economics (STIE-Hope) field should be more Akif for attaching banners, posters, and provide information about the dangers of smoking and enforce a no-smoking on campus